Title: Intimate Partner Violence: The Moderating Role of Personality Trait and Religion. - Isangha, Stanley Oloji; Ngwu, Christopher Ndubuisi; Iwuagwu, Anthony Obinna; Abonyi, Sunday Evaristus; Nnaji, Akuchukwu Oprah; Rahman, Farah Naz (Advances in Social Sciences Research Journal, 2021)
Objective: Intimate partner violence which is an aspect of family violence has most often than not affected peaceful family growth across the world, while it is largely portrayed that men are the sole perpetrators of IPV and women its victims. Statistics across countries in America, Asia, Europe and Africa have shown men to be victims as well, both in heterosexual and homosexual family, thus IPV can be perpetrated by both sexes just as they can also be victims. This study therefore assessed the moderating role of personality trait and religion on intimate partner violence in heterosexual relationship. Methods: Using a mixed method, 384 residents of Uyo metropolis were surveyed and 10 in-depth interviews was conducted among Psychology and Sociology lecturers from the University of Uyo Akwa Ibom state. The big five factor model served as its theoretical orientation. The big five personality inventory, religious orientation test and intimate partner violence propensity scale were used in generating data. Data were analyzed using SPSS version 20 software. Chi square test was used to test relationships while their long-run influence was ascertained using multiple and binary logistics linear regression analysis. Result: Findings show that majority of the respondents have abused their partners physically or psychologically. Findings show personality traits and religion as independent and joint predictors of intimate partner violence. Conclusion: It is recommended that clinicians, psychiatrists among other related professionals should always consider personality traits and religion when dealing with issues on IPV.